PERLINDUNGAN HUKUM TERHADAP PENGUASAAN HARTA BAWAAN DAN HARTA BERSAMA SETELAH PERCERAIAN MENURUT UU NO. 1 TAHUN 1974 TENTANG PERKAWINAN BERBASIS KEADILAN - Zulfiani Zulfiani (Jurnal Pembaharuan Hukum, 2016)
In the institution of marriage since the ancient times knew the mixing of marital property. Good treasure together and innate property. The setting of common property and assets native set out in Chapter VII, Article 35 paragraph (1) and (2) of Law No 1 of 1974 on Marriage. Possession of common property after divorce is divided into two / one-half possessions while carrying controlled by each party. And for the protection of the law against marital property agreement made marriage (prenuptial agreement) for the many different Islamic Religious Affairs in the Office of the Civil Registrar in front Perkawnian, while for the non-Muslims do in a Civil Registry in order to anticipate the consequences of the law of property in a marriage.